2005
DOI: 10.1002/ajh.20432
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between Budd‐Chiari syndrome and gemtuzumab ozogamicin treatment in a patient with refractory acute myelogenous leukemia

Abstract: Gemtuzumab ozogamicin (GO; CMA‐676; Mylotarg™) is a chemotherapeutic agent approved for the treatment of CD33‐positive acute myelogenous leukemia in patients of age 60 years or older after first relapse. Hepatic veno‐occlusive disease has been reported to develop as a late complication of gemtuzumab ozogamicin treatment. A patient who developed Budd‐Chiari Syndrome with hepatic vein thrombosis following treatment with GO is presented. This complication has not been previously reported, and it deserves to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In our case, BCS was likely secondary to undiagnosed AML on admission. On review of the literature, there are 10 reported cases of BCS in association with AML, of which seven cases were presented with BCS as an initial presentation of AML (Table 2) [5,[7][8][9][10][11][12][13][14]19]. Of the reported cases, seven cases occurred in APL, including one microgranular variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, BCS was likely secondary to undiagnosed AML on admission. On review of the literature, there are 10 reported cases of BCS in association with AML, of which seven cases were presented with BCS as an initial presentation of AML (Table 2) [5,[7][8][9][10][11][12][13][14]19]. Of the reported cases, seven cases occurred in APL, including one microgranular variant.…”
Section: Discussionmentioning
confidence: 99%
“…The patients may present with VTE as a presenting symptom of hematological malignancy [6]. There are only seven reported cases of acute myeloid leukemia (AML) presenting with acute BCS as the initial presentation in the literature [5,[7][8][9][10][11][12][13][14]. In patients presenting with acute BCS with ALF, a high index of suspicion and exclusion of underlying malignancy is a must, as it is a contraindication for liver transplantation (LT).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to HRT with estradiol and dydrogesterone, the Budd-Chiari syndrome in this case was suspected to be due to leukemia and HSCT used for its treatment. However, most cases of primary Budd-Chiari syndrome associated with leukemia are due to thrombosis associated with disseminated intravascular coagulopathy and rarely to intravenous infiltration of fungi from liver abscesses ( 5 , 6 ) or gemtuzumab ozogamicin ( 7 ). All of these conditions were considered to be different from the pathogenesis in this case, as they occur within a short period of time after the onset of leukemia and have an acute course.…”
Section: Discussionmentioning
confidence: 99%
“…Other serious toxicities also have been reported, such as a sensorimotor peripheral neuropathy mimicking Guillain-Barré syndrome [31], Budd-Chiari syndrome [32], and diffuse alveolar hemorrhage [33].…”
Section: Toxicitiesmentioning
confidence: 99%